Unexpected Encounters with Deep Time Enchantment. Bog Bodies, Crannogs and 'Otherworldly' sites. The materializing powers of disjunctures in time. Issue 4 (7th August 2016) - Fredengren, Christina
ABSTRACT: The topic of 'deep time' has recently gained attention in the field of environmental humanities. In contrast, heritage studies have a narrower focus on the role of the past in the present. This paper probes into how encounters with deep time, archaeology and heritage could play a role in environmental ethics and issues of intergenerational justice and care. People's meetings with intermingled temporalities, and collisions of past and present, are highlighted through the peculiar and disruptive affect of exceptional preservation in crannogs, bog bodies, wetlands and lakes. It is argued that such archaeology has the potential to produce 'enchantment' effects, understood as energising moments of startling presence, which can be powerfully deployed to move people from ethical thinking and reflection towards ethical action. However, in order to acknowledge the particular power of deep-time archaeological effects, and to realise the potentialities of heritage, it needs to be approached differently.